Sistem Pengembangan Karir Sekretaris Desa Setelah Pengangkatan Menjadi ASN - Amri Amri; Rudi Kurniawan (Asia-Pacific Journal of Public Policy, 2020)
This study aims to explore information on the career development system of the village secretary after being appointed as a civil servant (ASN). The location of the study was conducted at the North Aceh Civil Service and Human Resources Development Agency (BKPSDM) involving 10 informants who were determined based on purposive sampling. The results of the study found that there are still 322 active village secretaries who did not get career development as civil servants. From this research, it can be assumed that the village secretary career development system in North Aceh Regency has not been implemented completely. There are still barriers, including lack of awareness, low education, motivation, desire and aspirations to progress and develop, as well as low enthusiasm and enthusiasm of the village secretary. Besides, there is also a lack of attention from the stakeholder and never allowing taking part in training. Meanwhile, some efforts should be provided to support the career of the village secretary such as providing a coaching, direct superior directives, work motivation from the leadership and providing opportunities for training.